Characterising the KMP-11 and HSP-70 recombinant antigens' humoral immune response profile in chagasic patients - Steindel Mario; Cuellar Adriana; González John; Rosas Fernando; Velasco Víctor; Cucunubá Zulma; Thomas María; López Manuel; Flechas Ivonne; Puerta Concepción (BMC Infectious Diseases, 2009)
Abstract Background Antigen specificity and IgG subclass could be significant in the natural history of Chagas' disease. The relationship between the different stages of human Chagas' disease and the profiles of total IgG and its subclasses were thus analysed here; they were directed against a crude T. cruzi extract and three recombinant antigens: the T. cruzi kinetoplastid membrane protein-11 (rKMP-11), an internal fragment of the T. cruzi HSP-70 protein192-433, and the entire Trypanosoma rangeli HSP-70 protein. Methods Seventeen Brazilian acute chagasic patients, 50 Colombian chronic chagasic patients (21 indeterminate and 29 cardiopathic patients) and 30 healthy individuals were included. Total IgG and its subtypes directed against the above-mentioned recombinant antigens were determined by ELISA tests. Results The T. cruzi KMP-11 and T. rangeli HSP-70 recombinant proteins were able to distinguish both acute from chronic chagasic patients and infected people from healthy individuals. Specific antibodies to T. cruzi crude antigen in acute patients came from IgG3 and IgG4 subclasses whereas IgG1 and IgG3 were the prevalent isotypes in indeterminate and chronic chagasic patients. By contrast, the specific prominent antibodies in all disease stages against T. cruzi KMP-11 and T. rangeli HSP-70 recombinant antigens were the IgG1 subclass. Conclusion T. cruzi KMP-11 and the T. rangeli HSP-70 recombinant proteins may be explored together in the immunodiagnosis of Chagas' disease. Polarising the IgG1 subclass of the IgG response to T. cruzi KMP-11 and T. rangeli HSP-70 recombinant proteins could have important biological effects, taking into account that this is a complement fixing antibody.